Socialization of Islamic Financial Institution Literacy in MSMEs Upscale in DKI Jakarta: Sosialisasi Literasi Lembaga Keuangan Syariah pada UMKM Naik Kelas DKI Jakarta - Sufyati HS; Tati Handayani; Faisal Marzuki; Abdul Husen Zaelani (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The literacy level of the Indonesian people towards Islamic financial institutions is still deficient, especially in the Micro, Small and Medium Enterprises (MSME) sector. The low level of Islamic financial literacy makes MSMEs seek capital from illegal institutions, moneylenders or online loans due to the proliferation of low-interest offers and easy access to capital without complicated bureaucracy. Suppose we know that it is also easy to access business capital in Islamic financial institutions. Therefore, there is a need for socialization regarding the literacy of Islamic financial institutions in MSMEs. This socialization aims to increase information about the existence of Islamic financial institutions and products and services owned by Islamic financial institutions and to invite MSME actors domiciled in the DKI Jakarta area to abandon the concept of interest (usury). This method of implementing community service activities is still in the atmosphere of COVID.19 pandemic, so the implementation is carried out online (online). The implementation of the activity begins with the presentation of the material, simulations, giving questionnaires through the google form and evaluation. The results of the activities achieved are based on the answers of the participants who filled out the questionnaire after participating in the socialization activities for MSME actors, the level of understanding of knowledge on literacy of Islamic financial institutions, banking, and non-banking is average. The average is quite significant. The implementation of this activity implies a need for synergy between universities and the community, especially Muslims, to access Islamic financial institutions in daily life